SAT0156 Cryoglobulinemic Vasculitis: Study of 34 Patients from a Single Center According to the New Nomenclature of Vasculitis Of Chapel Hill 2012. (23rd January 2014) - Calvo-Río, V.; Loricera, J.; Ortiz-Sanjuán, F.; Crespo, J.; Martín Penagos, L.; Rueda-Gotor, J.; Martinez-Taboada, V.; González-Gay, M. A.; Blanco, R.
Abstract : Background: Cryoglobulinemic vasculitis (Vcrio) is characterized by the presence of circulating cryoglobulins usually affecting small blood vessel. The Nomenclature of Chapel Hill 1993 (A&R 1994;37:187) considered all VCrio generically. However, VCrio may be idiopathic (essential) or associated with chronic infections, mainly due to hepatitis C virus (HCV), autoimmune diseases and hematological malignancies. The new Nomenclature of Chapel Hill 2012 (A&R 2013:65:1) considered as Vcrio only the essential, and the remaining cases as Vcrio associated to other processes. Objectives: Our aim was to study the frequency and characteristics of Vcrio according to this new classification in a defined population. Methods: Study of a series of Vcrio from a universitary hospital. Circulating cryoglobulins (cryocrit>1%) and vasculitic involvement of a target organ, especially skin, peripheral nerve and/or kidney was required to make a diagnosis. For this purpose we used the criteria mentioned above (Chapel Hill-2012). According to them, VCrio were divided into primary and associated with other processes. A comparative study between both groups was performed. Results: We studied 34 patients (15 men/19 women) with a mean±SD age of 53±15 years (range, 27-81). The essential Vcrio was observed in 12 cases. In the remaining cases it was associated with one or more of the following: a) HCV (15 cases), b) HBV (2 cases), c) autoimmune disease (6 cases; 4 Sjögren´s syndrome, 1 RA, 1 sarcoidosis, 1 SLE, 1 primary billiary cirrhosis) and d)hematological disorders (4 cases, 2 Hodgkin lymphomas, 1 NHL and 1 MALT lymphoma). The comparative study between primary Vcrio versus secondary (expressed always in this order) showed that the clinical vasculitic manifestations were similar in both groups: cutaneous (92% vs 86%, p=0.6), joint (75% vs 55%, p=0.2), kidney (33% vs 41%, p=0.6), peripheral neuropathy (25% vs 36%, p=0.5), Raynaud's phenomenon (17% vs 14%, p=0.8), and digestive (8% vs 18%, p=0.4). The main laboratory findings were elevated ESR (75% vs 95%, p=0.1), leukocytosis (8% vs 5%, p=0.6), anemia (17% vs 50%, p=0.05). Immunological tests were determined in 29 cases being similar in both groups; positive Rheumatoid Factor (82% vs 83%, p=0.9) and decreased C3 and/or C4 (64% vs 56%, p=0.6). Positive Antinuclear Antibodies were more frequently observed in secondary Vcrio (0% vs 35%, p=0.02) and cryocrit in primary VCrio (25.5% vs 3%, p=0.02). Comparative study of treatment in primary Vcrio vs secondary was: a)NSAIDs (67% vs 20%, p=0.01), b)steroids (50% vs 71%, p=0.2), c)cytotoxic (40% vs 48%, p=0.7) and d)plasmapheresis (0% vs 18%, p=0.1). In 13.3% of patients with HCV-associated Vcrio combined antiviral therapy was used (interferon and ribavirin). After a median (IQR) of follow-up of 42 (8-99) months, relapses were observed in 45% vs 67%, (p=0.3) and complete recovery in 42% vs 13%, (p=0.9). Conclusions: Overall, most clinical and laboratory manifestations related to vasculitis in the setting of both primary VCrio and that associated-to other conditions are similar. In any case their differentiation following the Nomenclature of Chapel Hill-2012 is useful. Acknowledgements: This study was supported by grants from "Fondo de Investigaciones Sanitarias"PI12/00193 (Spain). This work was also partially supported by RETICS Program, RD08/0075 (RIER) from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None Declared